Fisherman’s Social Network in Fish Marketing Activities during The Covid-19 Pandemic (Case Study in Kampung Nelayan Untia, Makassar City) - Irwansyah, Irwansyah; Arief, Andi Adri; Wahid, Abdul; Fachry, Mardiana E.; Mustafa, Muhammad Dalvi (PONGGAWA : Journal of Fisheries Socio-Economic, 2022)
This study aims to find out to determine the form of social network for Grouper (Epinephelus sp.) fishermen in Untia Fisherman Village, Makassar City before the Covid-19 pandemic period and to determine the ability of Grouper (Epinephelus sp.) fishermen in building social networks. during the covid-19 pandemic in the Untia Fisherman's Village, Makassar City. This study uses descriptive qualitative and data collection techniques are observation and interviews using questionnaires. The sampling technique used snowball sampling with a total sample of 10 people. This research was conducted in March-April 2021 in Untia Fisherman's Village, Biringkanaya District, Makassar City with data analysis methods, namely data collection, data reduction, data display, leveraging and affirmation of conclusions (drawing conclusions and verification). The results of this study indicate that (1) there are three forms of fishermen's social networks, namely vertical social networks, vertical social networks and diagonal social networks (2) The ability of fishermen to build social networks is still quite low.